Antagonism of m3 Alleviates Type 2 Inflammation in Allergic Rhinitis Mice. Issue 3 (May 2023) - Chen, Yu; Huang, Aijie; Tan, Guolin; Liu, Honghui
Background: Type 2 immune cells play a pivotal role in allergic rhinitis (AR). Increasing evidence shows that inhibition of cholinergic nerve activity decreases the severity of airway diseases including asthma and AR. However, the role of the cholinergic receptor muscarinic 3 (m3) in type 2 inflammation in AR is unknown. Objective: We aimed to investigate the effect of m3 on the type 2 immune response, including both T helper 2 (Th2)-mediated and type 2 innate lymphocyte (ILC2)-mediated inflammation, in AR. Methods: Peripheral blood mononuclear cells (PBMCs) from human were cultured in vitro. Treatment with the m3 antagonist 1, 1-dimethyl-4-diphenylacetoxypiperidinium iodide (4-DAMP) was used. The percentages of Th2 and ILC2 cells in PBMCs were evaluated by flow cytometry. AR mouse models were established by house dust mite (HDM) sensitization, and treated with tiotropium intranasally. The expression of Th2 cytokines, ILC2 cytokines and related factors in the nasal mucosa was assessed by immunohistochemistry and quantitative real-time polymerase chain reaction. Serum HDM-specific immunoglobulin E (sIgE) level was detected by enzyme-linked immunosorbent assay. Results: Both Th2 and ILC2 percentages in PBMCs were decreased after 4-DAMP treatment. Similarly, the levels of Th2 cytokines (interleukin 4 [IL-4] and IL-13) and ILC2 cytokines and related factors (IL-25, IL-33, GATA3 and RORα) were significantly decreased in the nasal mucosa of AR mice after tiotropium treatment. Furthermore, tiotropium treatment decreased the nasal symptom score, the serum sIgE level and eosinophil infiltration in AR mice. In addition, tiotropium decreased phospholipase Cγ1 (PLCγ1), PLCγ2, nuclear factor of activated T cell 1 (NFATc1), and NFATc2 mRNA levels in AR mice. Conclusion: Antagonism of m3 alleviated type 2 inflammation in the nasal mucosa of AR mice.